A multi-sensing physical therapy assessment for children with cerebral palsy - Souza, R. (2017)
This work presents the development of a multi-sensing interface called Palsy Thera Sense, to provide information data obtained during physical therapy of the children with cerebral palsy. It allows the monitoring the children's motor skills, and provide metrics that can be later used for proper and effective training. This interface is based on distributed force measurement system characterized by two different load cells. The signals from signals from the load cells distributed on the level of a force platform and at the level of child's body support ropes that are tied on the cerebral palsy spider cage are acquired and wireless transmitted to a client computation platform. Thus different tests can be carried out including, center of forces measurements and gait simulations. These tests can be study of children balance during different activities such as serious game playing for upper limb rehabilitation. The interface shown to be an important tool that provide support to cerebral palsy rehabilitation process, and for objective evaluation of the patients during the rehabilitation period. Several experimental results are included in the paper highlighting the capabilities of the designed and implemented multi-sensing system.